Tension pneumothorax as a severe complication of endobronchial ultrasound-guided transbronchial fine needle aspiration of mediastinal lymph nodes - Gnass, Maciej; Szlubowski, Artur; Gil, Tomasz; Kocoń, Piotr; Ziętkiewicz, Mirosław; Twardowska, Magdalena; Kużdżał, Jarosław (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
This article presents a case report of a patient suffering from bullous emphysema and chronic obstructive pulmonary disease, who was diagnosed with tension pneumothorax after undergoing endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA). Tension pneumothorax is a severe but rare complication of EBUS-TBNA. It can result from lung injury caused by the biopsy needle or, in patients suffering from bullous emphysema, from spontaneous rupture of an emphysematous bulla resulting from increased pressure in the chest cavity during cough caused by bronchofiberoscope insertion. The authors emphasize that patients should be carefully monitored after the biopsy, and, in the case of complications, provided with treatment immediately in proper hospital conditions. Patients burdened with a high risk of complications should be identified before the procedure and monitored with extreme care after its completion.